Two new species and a new generic record of Asterinaceae on Mimusops elenji from Kerala - and D.K. AGARWAL, V.B. HOSAGOUDAR*, A. SABEENA (Indian Phytopathology, 2009)
This paper gives an account of two Asterinaceae members infecting the leaves of Mimusops elenji from Kerala. These are Asterina mimusopsidicola and Symphaster mimusopsidis. The genus Symphaster is reported here for the first time from India.